Influence of Load Test Scale on Prediction of Ultimate Bearing Capacity of Aggregate Pier Reinforced Clay - Sung-Ha Baek; Taeho Bong (Advances in Civil Engineering)
Predicting the bearing capacity of spread footings on aggregate pier-reinforced soil is particularly important for ground improvement. Various methods for predicting the bearing capacity of spread footings supported on aggregate pier-reinforced clay have been proposed. In addition, many fields or laboratory load tests have been conducted to identify the improvement effects of aggregate pier. However, no study has quantitatively compared the effect of the experimental scale on the prediction of bearing capacity. In this study, multiple linear regression analyses were performed for field and laboratory load tests, and the effects of the load test scale on bearing capacity prediction were identified. The sensitivity analysis showed that the prediction model for the laboratory load test (MLRL) exhibited a higher sensitivity for the undrained shear strength than that of the field load test model (MLRF). However, the sensitivity of the area replacement ratio of MLRL was less than half that of the MLRF. As the undrained shear strength increased, the predicted bearing capacity of the MLRL was larger than that of the MLRF owing to the influence of boundary conditions on the experimental equipment.